Composite MOF (Metal Organic Framework) material and application thereof in inhibiting growth of lithium dendrites

By coating organic inorganic composite porous MOF material on the lithium negative electrode of the lithium metal battery, a stable porous solid electrolyte layer is formed, which solves the safety problems caused by lithium dendrites, and achieves high cycle stability and low polarization performance of the lithium metal battery.

CN119798692AInactive Publication Date: 2025-04-11DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411965848.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium metal batteries, the growth of lithium dendrites leads to safety problems such as internal short circuits and thermal runaway, which limits the practical application of lithium metal batteries.

Method used

The organic and inorganic composite porous MOF material is used as the modified material for the lithium negative electrode. By forming a stable porous solid electrolyte layer (ASEI), the mechanical strength of SEI is enhanced, and the uniform deposition and peeling of lithium ions are adjusted, thereby inhibiting the growth of lithium dendrites.

Benefits of technology

Effectively slows down the increase in voltage polarization during lithium metal deposition/stripping, enhances the cycle stability of the battery, avoids the occurrence of short circuits, and achieves a stable cycle of low polarization, long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798692A_ABST
    Figure CN119798692A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a composite MOF (Metal Organic Framework) material and application thereof in inhibiting growth of lithium dendrites. The invention provides an organic-inorganic composite MOF (Metal Organic Framework) modified material which is of a self-assembled hexagonal prism-shaped porous structure, and a preparation method comprises the following steps: adding porphyrin, zirconium chloride and benzoic acid into an organic solvent; then adding deionized water as a regulator to form a mixed solution; and heating, washing, soaking and drying the obtained solution to obtain the organic-inorganic composite MOF material. According to the invention, the synthesized MOF material is coated on the surface of the lithium sheet to modify the lithium negative electrode so as to inhibit lithium dendrites, so that the performance of the battery is improved. And the preparation method has the advantages of simple operation, high repeatability, low cost and the like, and has important application value for the development of the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of MOF materials with porous structures, and in particular to a composite MOF material, a preparation method thereof and an application thereof in inhibiting the growth of lithium dendrites. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the increasing demand for high-energy-density batteries in fields such as electric vehicles, wearable devices, and energy storage systems, lithium metal batteries have become a research hotspot for the next generation of battery technology due to their high capacity and theoretical energy density. As a negative electrode material, lithium metal has extremely high specific capacity (3860 mAh / g) and negative potential (-3.04 V vs. SHE). Therefore, lithium metal batteries have great potential in improving energy density. However, during the charging and discharging process of lithium metal batteries, the deposition and stripping of lithium metal anodes will lead to the growth of lithium dendrites, resulting in safety problems such as internal short circuit and thermal runaway, thus limiting the practical application of lithium metal batteries. In lithium metal batteries, the formation of dendrites is one of the main reasons affecting the cycle life, safety, and stability of batteries. Lithium dendrites usually grow under the action of non-uniform electric fields, resulting in non-uniform lithium deposition on the electrode surface. Dendrites not only increase the internal resistance of the battery, but may also penetrate the diaphragm, causing internal short circuits, thereby causing safety accidents such as thermal runaway and battery fire. Therefore, inhibiting the growth of lithium dendrites and promoting uniform deposition of lithium have become one of the core goals of current lithium anode research. In order to overcome the problem of lithium dendrite growth, researchers have proposed a variety of solutions, including electrolyte additives, solid electrolytes, surface modification, and interface engineering based on different materials. In particular, it has become an effective strategy to modify the surface of the lithium negative electrode with a layer of functional materials to form an artificial protective layer. For example, materials such as solid electrolyte interface (SEI) layer, polymer coating, carbon-based materials and inorganic metal oxides are used for modification. However, most of these modification methods have problems such as unstable modification layer, poor reversibility, and poor conductivity to lithium ions, and have failed to fundamentally solve the dendrite problem.

[0004] In recent years, metal organic frameworks (MOFs) have been gradually introduced into the research of lithium batteries due to their highly adjustable pore structure, large specific surface area, and good chemical and thermal stability. The porosity of MOF materials makes them potential negative electrode modification materials for lithium metal batteries, which can provide larger lithium ion conductive channels and higher reaction activity. However, pure MOF materials may experience structural collapse or failure during battery cycling, affecting their stability in long-term use. Therefore, how to combine MOF materials with other materials to form more stable and high-performance composite materials has become an important direction for solving the problem of lithium dendrite growth.

[0005] Organic-inorganic composite MOF materials with intramolecular pores formed by self-assembly of organic ligands and inorganic metal ions or clusters combine the advantages of organic ligands and inorganic metal centers, and have excellent conductivity, structural stability and multifunctionality. By applying organic-inorganic composite MOF materials to lithium negative electrode modification, the stability of the electrode surface can be effectively improved, the deposition behavior of lithium ions can be controlled, and the growth of dendrites can be inhibited. Although some studies have attempted to apply MOF materials to lithium negative electrode modification, there are still certain challenges in their application mechanism, material optimization and performance improvement in actual batteries. Summary of the invention

[0006] In view of the problems existing in the above-mentioned prior art, the present invention is designed to provide an organic-inorganic composite MOF material that can inhibit the growth of dendrites of lithium negative electrode. The MOF material is coated on the surface of lithium negative electrode to form an artificial solid electrolyte layer (ASEI), which enhances the mechanical strength of SEI, and can effectively regulate the uniform deposition and stripping of lithium ions to inhibit the growth of lithium dendrites. It can greatly slow down the increase of voltage polarization during the lithium metal deposition / stripping process and enhance the cycle stability of the battery.

[0007] Based on the above technical effects, the present invention provides the following technical solutions: In a first aspect of the present invention, a composite MOF material is provided. The MOF material has the appearance of a purple crystalline powder, and is observed under an electron microscope as a stacked layered hexagonal prism. The X-ray powder diffraction spectrum is measured at 4.6°, 6.8°, 8.2°, and 2 θ ±0.2° has a characteristic peak.

[0008] Furthermore, the above MOF material has Figure 1 Similar X-ray powder diffraction patterns.

[0009] PCN-222 is a special type of metal organic framework, known for its unique properties and potential applications. One of its main known characteristics is that it has a high surface area and a clear porous structure. After comparison, the diffraction peak of the MOF material provided by the present invention is the same as the main structure of PCN-222, indicating that the MOF material provided by the present invention also has a rich porous coordination network. Combined with the results of electron microscopy (SEM) and transmission electron microscopy (TEM), the MOF material has a porous structure.

[0010] In a second aspect, a method for preparing the composite MOF material described in the first aspect is provided, comprising the following steps: adding 5, 10, 15, 20 tetrakis(4-carboxyphenyl)porphyrin, zirconium salt and benzoic acid to N,N-dimethylformamide (DMF), adding water as a regulator, and heating the resulting solution at 120-140°C for 17-25 hours; washing the obtained reaction precipitate, soaking it in an alcohol solution, and crystallizing it under a vacuum environment to obtain purple crystals.

[0011] During the research process of the above preparation method, it was found that the addition of H2O plays a vital role in the morphology control of the composite MOF material. The H2O molecule not only acts as a morphology regulator, but also as a structural agent, inducing the formation of a hierarchical MOF material with good two-dimensional nanosheets. The control group was synthesized in the same way, but without introducing H2O molecules as a regulator. In contrast, a small-sized crystalline zirconium-porphyrin cubic structure was obtained, showing a blocky morphology without a hierarchical structure. The morphology of the above material is of great significance to the lithium metal deposition / stripping performance in the modified lithium battery. According to the present invention, the above composite MOF material has a good performance at 1 mA / cm 2 At a current density of , the modified symmetric battery remained stable after 1800 hours of cycling, while the symmetric battery of the MOF material group prepared without adding water showed a sharp increase in polarization and even short circuit after 180 hours of cycling.

[0012] The dosage ratios of the 5, 10, 15, 20 tetrakis(4-carboxyphenyl)porphyrin, zirconium salt, benzoic acid, N,N-dimethylformamide and water are as follows: 90-110 mg: 120-160 mg: 5-6 g: 15-25 mL: 1200-1500 μL.

[0013] The zirconium salt is one of zirconium chloride and zirconium nitrate or a combination thereof, preferably zirconium chloride.

[0014] The heating is preferably carried out by heat radiation heating, which is a heating method that is relatively easy to implement in most production environments, such as heating in an oven.

[0015] The reaction precipitate can be separated by centrifugation, filtration, etc., and DMF is added to the separated precipitate for washing several times, and the washed precipitate is immersed in an alcohol solution for 22 to 26 hours. The alcohol solution is preferably a low-carbon alcohol, such as methanol or ethanol. In one embodiment verified by the present invention, ethanol is used.

[0016] The temperature of the above crystallization process is controlled at 55~65°C and the time is 18~25h.

[0017] In a third aspect, an application of the composite MOF material described in the first aspect in inhibiting the growth of lithium dendrites is provided.

[0018] Commonly used methods for inhibiting the growth of lithium dendrites in this field include: using solid electrolytes to prevent dendrite penetration, adding inhibitors to liquid electrolytes to improve lithium deposition, or surface modification of lithium negative electrodes. The above-mentioned composite MOF material coated on the surface of the lithium negative electrode can quickly form a porous solid electrolyte interface. On the one hand, it can increase the mechanical strength of the solid electrolyte interface layer, making it difficult for lithium to puncture. In addition, the porous structure of the composite MOF material can also guide the deposition of lithium. In a feasible implementation mode verified by the present invention, the above-mentioned composite MOF material can be used to prepare the passivation layer / SEI film of the lithium negative electrode.

[0019] In a fourth aspect, a modified lithium negative electrode is provided, wherein the surface of the modified lithium negative electrode has a passivation layer prepared from the above-mentioned composite MOF material.

[0020] Furthermore, the preparation method of the modified lithium negative electrode is as follows: the composite MOF material is added into an organic solvent to fully disperse it, and the dispersed solution is evenly spread on a lithium foil, and the obtained material is obtained after the solvent evaporates.

[0021] In the above preparation method, the organic solvent is preferably an organic reagent that is volatile at room temperature, including but not limited to one of ethanol, dimethylformamide (DMF), ethylene glycol dimethyl ether (DME), ether, pentane, and acetone. In one embodiment verified by the present invention, the organic solvent is DME, and the ratio of the composite MOF material to DME is 50 mg: 8-12 mL, and it is fully stirred to form a uniform solution.

[0022] The dosage of the above solution is as follows: the lithium foil has a diameter of 10 mm and the solution dosage is 20~30μL.

[0023] In a fifth aspect, a lithium metal symmetrical battery is provided, wherein the battery has the modified lithium negative electrode described in the fourth aspect.

[0024] In one embodiment verified by the present invention, the electrolyte of the symmetrical battery is a 0.8~1.2M LiTFSI solution, the solvent of the electrolyte is dioxolane (DOL) / ethylene glycol dimethyl ether (DME) (1:0.8~1.2, volume ratio), 1.5~2.6wt% LiNO3 is added to the electrolyte, and the battery separator is made of glass fiber.

[0025] In a sixth aspect, a lithium metal full battery is provided, wherein the full battery has the modified lithium negative electrode described in the fourth aspect.

[0026] In one embodiment verified by the present invention, in the above-mentioned lithium metal full battery, the separator is GlassFiber, the electrolyte is LiPF6 electrolyte, and the positive electrode is lithium nickel cobalt manganese oxide NCM811.

[0027] When the modified lithium negative electrode is used in lithium metal batteries, the formed ASEI has good interface stability. The metal lithium surface of the symmetrical battery remains smooth and dense after long cycles, avoiding short circuits. The NCM811 full battery can stably cycle at low polarization for at least 350 cycles.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The organic-inorganic composite porous MOF material of the present invention has an ordered porous structure. When applied to the modification of the lithium negative electrode, a stable SEI film can be formed. The porous structure provides a uniform deposition channel for lithium ions, which can effectively increase the diffusion rate of lithium ions and induce uniform deposition and stripping of lithium ions. Through the application of modified MOF materials, symmetrical batteries avoid short circuits, achieve low polarization, long-life stable cycles, and NCM811 full batteries achieve at least 350 high-capacity reversible cycles. The method of the present invention has a simple production process, is suitable for large-scale applications, and is of great significance to the development of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0030] Figure 1 is the XRD pattern of the composite MOF material described in Example 1; Figure 2 SEM (A) and TEM (B) images of the composite MOF material described in Example 1; Figure 3 It is a schematic diagram of the method for modifying the lithium negative electrode in Example 4 and a schematic diagram of the lithium metal symmetric battery structure of the lithium battery in Example 5; Figure 4 The modified lithium negative electrode described in Example 5 and the pure lithium negative electrode are subjected to a current density of 1 mA / cm2 Cyclic curve of lithium metal deposition / stripping process; Figure 5 The modified lithium negative electrode described in Example 5 and the pure lithium negative electrode are subjected to a current density of 3 mA / cm 2 Cyclic curve of lithium metal deposition / stripping process; Figure 6 The morphology of the metal lithium surface after the symmetrical battery with the modified lithium negative electrode described in Example 5 was cycled for 200 hours; Figure 7 is a typical charge and discharge curve of the Li-NCM811 battery in Example 6 in the first 200 cycles; Figure 8 This is a morphology diagram of the composite MOF material (without water added) described in Comparative Example 1; Fig. 9 The modified lithium negative electrode in Comparative Example 1 was subjected to a current density of 1 mA / cm 2 Cyclic curve of lithium metal deposition / stripping process; Fig.10 This is a typical charge and discharge curve of the Li-NCM811 battery in Comparative Example 1 in the first 200 cycles. DETAILED DESCRIPTION

[0031] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0032] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0034] Example 1 In this embodiment, a composite MOF material and preparation process are provided, comprising the following steps: 5, 10, 15, 20 tetrakis (4-carboxyphenyl) porphyrin (H2TCPP, 100 mg), zirconium chloride (ZrCl4, 150 mg) and benzoic acid (BA, 5.4 g) are added to N, N-dimethylformamide (DMF, 20 mL). Then, 1500 μL H2O is added as a regulator to form a dark green solution. The dark green solution is transferred to a 25 mL bottle and heated in an oven at 130 ° C for 20 hours. After cooling to room temperature, the resulting precipitate is washed with DMF and filtered, and then soaked in ethanol for 24 hours. Finally, the precipitate is filtered and heated in a vacuum at 60 ° C for 24 hours, and then purple crystals are obtained, which is the composite MOF material.

[0035] Its XRD Figure 1 As shown in FIG. 1 , the diffraction peak corresponds to the zirconium-based porphyrin metal organic framework material PCN-222, which proves that the composite MOF prepared in this embodiment has a porous coordination network similar to PCN-222. Figure 2 As shown in A, TEM Figure 2 As shown in B, it can be seen that the MOF material is self-assembled and aggregated by stacked layered hexagonal prisms, thus exhibiting a porous morphology.

[0036] Example 2 In this embodiment, another composite MOF material and preparation process are provided, comprising the following steps: 5, 10, 15, 20 tetrakis (4-carboxyphenyl) porphyrin (H2TCPP, 90 mg), zirconium chloride (ZrCl4, 120 mg) and benzoic acid (BA, 5.0 g) are added to N, N-dimethylformamide (DMF, 15 mL). Then, 1200 μL H2O is added as a regulator to form a dark green solution. The dark green solution is transferred to a 25 mL bottle and heated in an oven at 120 ° C for 25 hours. After cooling to room temperature, the resulting precipitate is washed with DMF and filtered, and then soaked in ethanol for 20 hours. Finally, the precipitate is filtered and heated in a vacuum at 55 ° C for 25 hours, and then purple crystals are obtained, which are the composite MOF material.

[0037] Example 3 In this embodiment, another composite MOF material and preparation process are provided, comprising the following steps: 5, 10, 15, 20 tetrakis (4-carboxyphenyl) porphyrin (H2TCPP, 110 mg), zirconium chloride (ZrCl4, 160 mg) and benzoic acid (BA, 6.0 g) are added to N, N-dimethylformamide (DMF, 25 mL). Then, 1400 μL H2O is added as a regulator to form a dark green solution. The dark green solution is transferred to a 25 mL bottle and heated in an oven at 140 ° C for 17 hours. After cooling to room temperature, the resulting precipitate is washed with DMF and filtered, and then soaked in ethanol for 18 hours. Finally, the precipitate is filtered and heated in a vacuum at 65 ° C for 18 hours, and then purple crystals are obtained, which are the composite MOF material.

[0038] Example 4 In this embodiment, a method for modifying a lithium negative electrode is provided, wherein the MOF material in the above embodiment 1 is used to construct a porous solid electrolyte interface on the lithium surface: like Figure 3 As shown, in order to evenly disperse the MOF powder on the surface of the lithium foil, 50 mg of the prepared MOF powder was dissolved in 10 mL of DME solvent and magnetically stirred for 24 hours to form a uniform solution. Afterwards, for a lithium foil with a diameter of 10 mm, 25 μL of the solution was pipetted and dropped onto the surface of the lithium foil. During this process, the purple solution spread evenly on the surface of the lithium foil, and the solvent evaporated within a few seconds, leaving the MOF powder evenly distributed on the surface of the lithium foil, which successfully constructed a porous solid electrolyte interface (SEI).

[0039] Example 5 In this embodiment, a lithium metal symmetric battery is provided, using the porous solid electrolyte interface constructed in the above embodiment 4, and the assembly and testing steps are as follows: All electrochemical measurements were performed using CR2032-type button cells assembled in an argon-filled glove box with water and oxygen values ​​less than 0.1 ppm. Li|Li symmetric cells were assembled from lithium foil treated as described in Example 4, and the electrolyte was a 1M LiTFSI solution in DOL / DME (1:1, volume ratio) with the addition of 2wt% LiNO3. In these cells, glass fiber was used as a separator. A fixed amount of lithium was electroplated onto the working electrode at different current densities, followed by lithium stripping / deposition, to evaluate the effectiveness of the artificial solid electrolyte interface (ASEI) in preventing lithium dendrite growth.

[0040] The assembled 2032 button-type symmetrical battery was charged and discharged on a LAND electrochemical workstation at 1 mA / cm 2At a current density of , the battery is first charged at a constant current for 2 hours, then discharged at a constant current for 2 hours, the voltage polarization difference during the deposition / stripping process of metallic lithium is detected, and the cycle is carried out in this step. Figure 4 and Figure 5 The lithium anode modified by composite MOF material and the pure lithium anode have a current density of 1 mA / cm 2 With 3mA / cm 2 The cyclic curve of lithium metal deposition / stripping process under the condition of 1 mA / cm2 shows that the modified lithium negative electrode avoids short circuit at both current densities and demonstrates long-life low polarization cycle. 2 At a current density of 3 mA / cm, the polarization voltage of the modified symmetric battery can still be maintained at about 75 mV after 1800 hours of cycling, while the pure lithium negative electrode symmetric battery has already short-circuited after 200 hours of cycling, which is because the lithium dendrites have grown through the separator. 2 Under the conditions of , the deposition / stripping time is kept at 1 hour, and the modified symmetric battery can still cycle for 500 hours, and the polarization voltage is maintained at about 130 mV. After the symmetric battery has been cycled a certain number of times, the battery is disassembled in a glove box filled with argon, the metal lithium sheet is taken out, washed several times in the electrolyte solvent DGM, dried naturally, and placed in a scanning electron microscope under argon protection for morphology observation. Figure 6 1 mA / cm 2 The morphology of the metallic lithium surface after the symmetrical battery with modified lithium negative electrode was cycled for 200 hours under the current density. As can be seen from the figure, the lithium metal surface after the cycle is still smooth and dense, confirming that the growth of negative electrode lithium dendrites is effectively suppressed.

[0041] Example 6 In this embodiment, a Li-NCM811 full battery with a modified lithium negative electrode is provided, and the assembly and testing steps are as follows: 1. Preparation of NCM811 positive electrode material NCM811 powder was purchased from Hefei Kejing Material Technology Co., Ltd. 450 mg of NCM811 powder, 25 mg of super carbon (Super C) and 25 mg of polyvinylidene fluoride (PVDF, concentration of 20 mg / μl) binder were mixed in N-methyl-2-pyrrolidone (NMP) solvent. The mixture was ground into a uniform slurry using an agate mortar for 10-15 minutes and then evenly coated on an area of ​​50 mm using a coater. 2 The vacuum-dried aluminum foil loaded with active substances was weighed again, bagged, and placed in a glove box.

[0042] 2. Battery assembly and testing The assembly of 2032 button cells was carried out in an argon glove box with a water value and an oxygen value of less than 0.1 ppm. The specific process is to use the modified lithium sheet described in Example 4 as the negative electrode, use GlassFiber as a diaphragm, add 120 μL of LiPF6 electrolyte, and then attach the positive electrode sheet carrying the active material to assemble a Li-NCM811 lithium metal full battery, and use a pure lithium negative electrode as a comparison. The assembled battery was charged and discharged on the LAND electrochemical workstation with a voltage range of 3-4.5 V and a current rate of 1C (1C corresponds to the current density required for the NCM811 positive electrode sheet to be fully charged in 1 hour with a theoretical specific capacity of 280 mAh / g). Figure 7 This is a typical charge and discharge curve of the Li-NCM811 battery in the first 200 cycles. Since lithium dendrites are suppressed, the morphology of the lithium negative electrode is significantly improved. The full battery modified by the modified lithium negative electrode shows higher specific capacity and cycle number, lower polarization and capacity attenuation.

[0043] Comparative Example 1 In this embodiment, another composite MOF material (without water) is provided. The difference from Example 1 is that no water is added as a regulator. The morphology of the synthesized material is as follows Figure 8 As shown, it shows a block morphology without a layered structure. The battery assembly and test conditions are the same as those in Examples 5 and 6. The lithium metal symmetric battery assembled with the composite MOF material prepared without adding water has a modified lithium negative electrode at a current density of 1 mA / cm 2 The cycle curve of lithium metal deposition / stripping process is as follows Fig. 9 As shown in Figure 2, the polarization of the symmetrical battery suddenly increases after 160 hours of stable cycling. The typical charge and discharge curves of the NCM811 full battery assembled with the composite MOF material prepared without adding water in the first 200 cycles are shown in Figure 2. Fig.10 As shown in the figure, from the charge and discharge curve of the full battery, the capacity of the full battery is relatively low and decays rapidly, and the polarization is greatly increased. The overall electrochemical performance is poor.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite MOF material, characterized in that: The MOF material has the appearance of purple crystalline powder, and is observed as stacked layered hexagonal prisms under an electron microscope. The X-ray powder diffraction spectrum shows that the MOF material has the following characteristics: θ ±0.2° has a characteristic peak.

2. The composite MOF material according to claim 1, characterized in that: The MOF material has an X-ray powder diffraction pattern similar to that in FIG1 .

3. The method for preparing the composite MOF material according to claim 1 or 2, characterized in that: The method comprises the following steps: adding 5, 10, 15, 20 tetrakis (4-carboxyphenyl) porphyrin, zirconium salt and benzoic acid into DMF, adding water as a regulator, heating the obtained solution at 120-140°C for 17-25 hours; washing the obtained reaction precipitate, soaking it in an alcohol solution, and crystallizing it under a vacuum environment to obtain purple crystals.

4. The preparation method according to claim 3, characterized in that: The dosage ratios of the 5, 10, 15, 20 tetrakis(4-carboxyphenyl)porphyrin, zirconium salt, benzoic acid, N,N-dimethylformamide and water are as follows: 90-110 mg: 120-160 mg: 5-6 g: 15-25 mL: 1200-1500 μL.

5. The preparation method according to claim 3, characterized in that: The zirconium salt is one of zirconium chloride and zirconium nitrate or a combination thereof, preferably zirconium chloride.

6. The preparation method according to claim 3, characterized in that: The heating is preferably carried out by heat radiation heating, and further, the heating is carried out in an oven; Alternatively, the reaction precipitate is separated by centrifugation or filtration, DMF is added to the separated precipitate for washing several times, and the washed precipitate is immersed in an alcohol solution for 22 to 26 hours; the alcohol solution is preferably a low-carbon alcohol, and further, ethanol; Alternatively, the temperature of the crystallization process is controlled at 55-65° C. and the time is 18-25 hours.

7. Use of the composite MOF material according to claim 1 or 2 in inhibiting the growth of lithium dendrites.

8. A modified lithium negative electrode, characterized in that The modified lithium negative electrode has a passivation layer on its surface, which is prepared using the composite MOF material according to claim 1 or 2; Furthermore, the preparation method of the modified lithium negative electrode is as follows: adding the composite MOF material into an organic solvent to fully disperse it, spreading the dispersed solution evenly on a lithium foil, and obtaining the modified lithium negative electrode after the solvent evaporates; The organic solvent is preferably an organic reagent that is volatile at room temperature, including but not limited to one of ethanol, DMF, DME, ether, pentane, and acetone; Furthermore, the organic solvent is DME, and the ratio of the composite MOF material to DME is 50 mg: 8-12 mL; The dropwise dosage of the solution is as follows: the lithium foil has a diameter of 10 mm and the solution dosage is 20-30 μL.

9. A lithium metal symmetrical battery, characterized in that: The battery has the modified lithium negative electrode according to claim 8; The electrolyte of the symmetrical battery is a 0.8-1.2M LiTFSI solution, the solvent of the electrolyte is dioxolane / ethylene glycol dimethyl ether, 1.5-2.6wt% of LiNO3 is added to the electrolyte, and the battery separator is glass fiber.

10. A lithium metal full battery, characterized in that: The full battery has the modified lithium negative electrode according to claim 8; In the lithium metal full battery, the separator is GlassFiber, the electrolyte is LiPF6 electrolyte, and the positive electrode is lithium nickel cobalt manganese oxide NCM811.

Citation Information

Patent Citations

  • Lithium sheet passivation method and application

    CN113889602A

  • MOFs (Metal-Organic Frameworks) nano array composite material grown on copper foil in situ and preparation method and application thereof

    CN117352637A

  • High-magnification artificial SEI material and application thereof

    CN118117094A

  • Preparation method and application of one-dimensional MOFs-based solid electrolyte

    CN118281355A